Low cairns, long cists and symbol stones - Ashmore, Patrick J (Proceedings of the Society of Antiquaries of Scotland, 1981)
Low mounds surrounded by rectilinear or circular ditches and low rectilinear and circular kerbed cairns, both groups covering extended inhumation burials, represent a funerary tradition of the pre-Viking Iron Age, predominantly in N Scotland. Sometimes forming cemeteries, these mounds and cairns are loosely associated with Pictish symbol stones, and a possible origin in La Tène burial tradition is suggested. A R